2012
DOI: 10.1111/j.1524-4725.2012.02520.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonmelanoma Skin Cancer in Solid Organ Transplant Recipients: Update on Epidemiology, Risk Factors, and Management

Abstract: Background Nonmelanoma skin cancers (NMSC) are the most frequently observed cancers in solid organ transplant recipients (SOTR) and may have a significant disease burden. Objective To provide an update regarding the epidemiology and management of NMSC in SOTR. Results Ten‐year incidence rates range from 10% in Italy to 20% in Northern Europe to 70% in Australia. More than 50% of NMSC are located on sun‐exposed areas (head, dorsum of hands). Many risk factors have been identified, including age at transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 87 publications
(299 reference statements)
3
73
0
8
Order By: Relevance
“…Seroepidemiological studies have associated skin cancer in organ transplant recipients with the presence of anti-b-HPV antibodies, and PCR-based studies have identified b-HPV DNA in over 80% of skin tumors from these patients. 22,[35][36][37][38][39][40][41][42][43] Despite these findings, a causal role of these viruses has been difficult to verify because of their ubiquitous prevalence in the general population and their absence in some cancers. 25,44 The major weakness of the available studies is that the proposed association is mostly based on the presence of viral DNA in tumor tissues or positive antibody responses.…”
mentioning
confidence: 99%
“…Seroepidemiological studies have associated skin cancer in organ transplant recipients with the presence of anti-b-HPV antibodies, and PCR-based studies have identified b-HPV DNA in over 80% of skin tumors from these patients. 22,[35][36][37][38][39][40][41][42][43] Despite these findings, a causal role of these viruses has been difficult to verify because of their ubiquitous prevalence in the general population and their absence in some cancers. 25,44 The major weakness of the available studies is that the proposed association is mostly based on the presence of viral DNA in tumor tissues or positive antibody responses.…”
mentioning
confidence: 99%
“…SCCs in the immunosuppressed are clinically harder to diagnose than in the immunocompetent and are more likely to metastasise. Advice on sun avoidance is thus particularly important to renal allograft recipients, and these patients require regular screening, and a high index of suspicion from their dermatologist [14] .…”
mentioning
confidence: 99%
“…Risk factors include Ultraviolet radiation exposure [1], use of tanning beds, [2] host factors such as eye and hair color, skin type, and immunosuppressed states seen in conditions like organ transplantation and HIV, as well as in genetic disorders like Gorlin syndrome, Xeroderma pigmentosum and albinism [3][4][5].…”
Section: Discussionmentioning
confidence: 99%